1997
DOI: 10.1021/la960092z
|View full text |Cite
|
Sign up to set email alerts
|

Surface Heterogeneity of C60 As Studied by Infrared Spectroscopy of Adsorbed CO and Adsorption Potential Calculations

Abstract: In our recent investigation of the IR spectrum of CO physically adsorbed on C60 films, two well-resolved absorption bands at 2135 and 2128 cm -1 were found, suggesting that the molecule is adsorbed on two different sites. To determine the nature of these adsorption sites, calculations of adsorption potentials and spectral shifts for the CO/C60 system were performed. The calculations were done for the fcc (100), fcc ( 111) hcp (001), and hcp (111) surface planes. In the calculations the 6-exponential and the Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…As shown in Figure 4, the intensity ratio of the absorption at ν =2125 cm −1 versus that at ν =2112 cm −1 is approximately 35:65, independent of the fraction of CO@ 1 present. This case contrasts with that of exohedral CO absorptions, in which the ratio is known to be dependent on the equilibrium pressure of CO 18a. The presence of two absorption bands indicates that there are two distinct orientations for the trapped CO on the IR time scale (picoseconds) whereas there must be rapid interchange between these states on the NMR time scale (milli‐ to microseconds) to account for the single resonance in the 13 C NMR spectrum.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…As shown in Figure 4, the intensity ratio of the absorption at ν =2125 cm −1 versus that at ν =2112 cm −1 is approximately 35:65, independent of the fraction of CO@ 1 present. This case contrasts with that of exohedral CO absorptions, in which the ratio is known to be dependent on the equilibrium pressure of CO 18a. The presence of two absorption bands indicates that there are two distinct orientations for the trapped CO on the IR time scale (picoseconds) whereas there must be rapid interchange between these states on the NMR time scale (milli‐ to microseconds) to account for the single resonance in the 13 C NMR spectrum.…”
Section: Methodsmentioning
confidence: 89%
“…Carbon monoxide absorbed on the exohedral surface of C 60 is known to disappear under reduced pressure, even at 77 K 18a. In contrast, CO@ 1 was relatively stable under reduced pressure even at ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The adsorption in these three sites develops into three distinct adsorption layers. The existence of the variety of favorable adsorption sites and the sequence of the adsorption on the surface of C 60 crystal have been observed in experimental studies [7][8][9]. Fig.…”
Section: Introductionmentioning
confidence: 88%
“…The adsorption of N 2 [4][5][6], Kr [4], and Ar [6] near 77 K were measured and the isotherms were found to be of type II. The surface heterogeneity of the C 60 crystal has been examined by infrared spectroscopy of adsorbed CO, and the spectral shifts indicated that different types of adsorption sites exist on the surface [7,8]. The adsorption energy distribution on the C 60 surface using hexane and heptane as probes revealed that there are three distinct families of adsorption sites [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of graphite, those aromatic clusters are parallel graphene layers. For char, it is known from solid-state 13 C NMR experiments that it has structures of randomly connected graphene clusters consisting of 12-25 aromatic carbon atoms (3-7 benzene rings). 30 Since an electron does not delocalize through single bonds efficiently, it is reasonable to assume that the reactivity of each graphene cluster is not affected by the remaining char structure.…”
Section: Computational Detailsmentioning
confidence: 99%